Trace of Positive Integer Power of Squared Special Matrix - Rahmawati Rahmawati; Aryati Citra; Fitri Aryani; Corry Corazon Marzuki; Yuslenita Muda (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2021)
The rectangle matrix to be discussed in this research is a special matrix where each entry in each line has the same value which is notated by An. The main aim of this paper is to find the general form of the matrix trace An powered positive integer m. To prove whether the general form of the matrix trace of An powered positive integer can be confirmed, mathematics induction and direct proof are used.